Problems and Optimization Strategies of Enterprise Risk Management and Internal Control—Taking the Kobayashi Pharmaceutical Red Yeast Rice Dispute as an Example - Sun, Wanye (Journal of Global Economy, Business and Finance, 2025)
In the context of global competition, the failure of corporate risk management and internal control may lead to serious crises. This paper takes the Kobayashi Pharmaceutical Red Yeast Incident as an example and analyzes its risk management and internal control deficiencies based on the COSO framework. The study found that Kobayashi Pharmaceutical’s risk identification was insufficient, assessment biased, and response was delayed, and internal control had information disclosure delays, irrational decision-making, and supply chain loopholes. For the above problems, this paper combines the PIML cycle model and proposes optimization paths such as strengthening risk strategy planning, dynamic assessment mechanism, and experience internalization, which provides a practical reference for enterprises to improve risk prevention and control effectiveness and improve internal control systems, and also warns food safety supervision and industry risk management.